Work in the Intersections: A Black Feminist Disability Framework - Bailey, Moya; Mobley, Izetta Autumn (Gender & Society, 2019)
A Black feminist disability framework allows for methodological considerations of the intersectional nature of oppression. Our work in this article is twofold: to acknowledge the need to consider disability in Black Studies and race in Disability Studies, and to forward an intersectional framework that considers race, gender, and disability to address the gaps in both Black Studies and Disability Studies. By employing a Black feminist disability framework, scholars of African American and Black Studies, Women’s, Gender, and Sexuality Studies, and Disability Studies have a flexible and useful methodology through which to consider the historical, social, cultural, political, and economic reverberations of disability.
Keywords: EDI; afro-féminisme; approches et analyses; capacitisme; care; cours; discipline; féminisme afroaméricain; histoire et politique; intersectionnalité; philosophie; premier cycle; racisme; ressource en ligne; santé; sciences humaines; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études de genres

Domestic violence at the intersections of race, class, and gender: challenges and contributions to understanding violence against marginalized women in diverse communities - Sokoloff, Natalie J; Dupont, Ida (Violence against women, 2005)
This article provides a comprehensive review of the emerging domestic violence literature using a race, class, gender, sexual orientation intersectional analysis and structural framework fostered by women of color and their allies to understand the experiences and contexts of domestic violence for marginalized women in U.S. society. The first half of the article lays out a series of challenges that an intersectional analysis grounded in a structural framework provides for understanding the role of culture in domestic violence. The second half of the article points to major contributions of such an approach to feminist methods and practices in working with battered women on the margins of society.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; care; corps; cours; criminologie; discipline; féminisme afroaméricain; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; thématiques; violences; états-unis